Skills in Preparing Mathematics Teaching Modules and Their Correlation with Skills in Providing Learning Variations for Prospective Elementary School Teachers - Wibowo, Sigit; Yuniawatika; Murti, Rahayu Condro; Wuryandani, Wuri; Purnomo, Yoppy Wahyu (MIMBAR PGSD Undiksha, 2024)
The many demands in designing mathematics learning mean that some teachers and prospective mathematics teachers are unable to carry it out well. This research aims to analyze the relationship between students' skills in compiling mathematics teaching modules and their skills in carrying out learning variations. This research uses quantitative methods. A total of 3 classes with a total of 106 students were the subjects of this research, namely students. Researchers used purposive sampling technique. The data collection techniques used were observation, interviews and documentation. The quantitative data analysis technique uses the Pearson Product Moment correlation test. Based on the research results, it was found that as many as 23% of students were able to compose the teaching module as a whole well. The skill of preparing teaching modules has a positive correlation with the skill of carrying out learning variations. Based on the Pearson Product Moment correlation test, the significance value (2-tailed) is 0.000 < 0.05, with a Pearson Correlation value of 0.840. This shows that there is a very strong correlation between the skills in preparing teaching modules and the skills in creating variations. Students who prepare teaching modules, especially the core components of good learning, have a fairly calm demeanor when carrying out learning simulations. When performance is calm, variations in learning can be seen. Practicing students will be able to make learning more interactive.